Dinamika Posisi Identitas Etnis Tionghoa dalam Tinjauan Teori Identitas Sosial - Eriyanti, Fitri (Jurnal Demokrasi, 2006)
Basically, each individual wished to have a positive social identity. In the point of view of social identity theory, the wishes to have positive social identity is viewed as an important psychological drive in individual actions at all social interactions. All this time, there are so many policies of Indonesian government that made the position of Indonesian-Chinese identity to be marginalized, both in colonial and independence eras. The dynamics of position of Indonesian-Chinese identity are basically related to the treatment of government. It seemed that the efforts to have positive social identity, the social mobility of the Indonesian-Chinese varied and depended on the perception of each group in connecting with how to improve theirselves images. Besides, there isÂ  also a tendency that they tried to make social changes through the improvisation of theirselves images from their Chineseâ€™s identity. Kata kunci: Posisi, Identitas Etnis, Identitas Sosial, Interaksi Sosial, Etnis Tionghoa